Ammonia-induced inhibition of manure-based continuous biomethanation process under different organic loading rates and associated microbial community dynamics. Issue 6 (January 2021) - Christou, M.L.; Vasileiadis, S.; Kalamaras, S.D.; Karpouzas, D.G.; Angelidaki, I.; Kotsopoulos, T.A.
Highlights: Synergetic stress of high VFAs and ammonia levels occurred during AD process. H2 -dependent methanogenesis tend to dominate under ammonia stressed conditions. Archaea relative abundance was decreased in all reactors under high ammonia level. Graphical abstract: Abstract: Three Continuously Stirred Tank Reactors (CTSRs) were operating at steady state conditions with Organic Loading Rates (OLR) of 2.09, 3.024 and 4.0 g VS L −1 d −1 . Glucose was used as the sole factor for increasing the OLR, linking the increase of the OLR with the C/N ratio increase. The reactors were stressed by increasing the ammonia concentration to 5 g L −1 from 1.862 g L −1 . The results showed elevating inhibition of the anaerobic process by increasing the C/N ratio just by increasing the OLR, under the high ammonia concentration. A different response of the bacterial and archaeal community under ammonia stressed conditions was also observed. Under the high ammonia concentration, hydrogen-depended methylotrophic was the dominant methanogenesis route at OLR of 2.09 g VS L −1 d −1, while the hydrogenotrophic route was the dominant at the high OLR of 4 g VS L −1 d −1, which coincided with high acetate and propionate concentrations.